Alcohol consumption decreases lactate clearance in acutely injured patients. Issue 9 (September 2016) - Dezman, Zachary D.W.; Comer, Angela C.; Narayan, Mayur; Scalea, Thomas M.; Hirshon, Jon Mark; Smith, Gordon S.
Abstract: Introduction: Alcohol, a common risk factor for injury, has direct toxic effects on the liver. The use of lactate clearance has been well described as an indicator of the adequacy of resuscitation in injured patients. We investigated whether acutely injured patients with positive blood alcohol content (+BAC) had less lactate clearance than sober patients. Methods: We conducted a retrospective cohort study of acutely injured patients treated at an urban Level 1 trauma centre between January 2010 and December 2012. Blood alcohol and venous lactate levels were measured on all patients at the time of arrival. Study subjects were patients transported directly from the scene of injury, who had an elevated lactate concentration on arrival (≥3.0 mmol/L) and at least one subsequent lactate measurement within 24 h after admission. Lactate clearance ([Lactate1 − Lactate2 ]/Lactate1 ) was calculated for all patients. Chi-squared tests were used to compare values from sober and intoxicated subjects. Lactate clearance was plotted against alcohol levels and stratified by age and Injury Severity Score (ISS). Results: Serial lactate concentration measurements were obtained in 3910 patients; 1674 of them had +BAC. Patients with +BAC were younger (mean age: 36.6 [SD 14.7] vs 41.0 [SD 19.9] years [ p = 0.0001]), were more often male (83.4% vs 75.9% [ p = 0.0001]), had more minor injuries (ISS < 9) (33.8% vs 27.1% [ p = 0.0001]), had a lower in-hospital mortality rate (1.4% vs 3.9% [ p = 0.0001]), but also had lower average lactate clearance (37.8% vs 47.6% [ p = 0.0001]). The lactate clearance of the sober patients (47.6 [SD 33.5]) was twice that of those with +BAC >400 (23.5 [SD 6.5]). Lactate clearance decreased with increasing BAC irrespective of age and ISS. Conclusions: In a large group of acutely injured patients, a dose-dependent decrease in lactate clearance was seen in those with elevated BAC. This relationship will cause a falsely elevated lactate reading or prolong lactate clearance and should be taken into account when evaluating patients with +BAC.